Temporal trends in Takotsubo syndrome: results from the International Takotsubo Registry - Schweigert, Victoria-Anne; Cammann, Victoria Lucia; Crisci, Giulia; Gilhofer, Thomas; Schlenker, Rabea; Niederseer, David; Chen, Shaojie; Ebrahimi, Ramin; Wenzl, Florian; Würdinger, Michael; Citro, Rodolfo; Vecchione, Carmine; et al. (Journal of the American College of Cardiology, 2024)
Background - The perception of takotsubo syndrome (TTS) has evolved significantly over the years, primarily driven by increased recognition of acute complications and mortality. - Objectives - This study aimed to explore temporal trends in demographic patterns, risk factors, clinical presentations, and outcomes in patients with TTS. - Methods - Patients diagnosed with TTS between 2004 and 2021 were enrolled from the InterTAK (International Takotsubo) registry. To assess temporal trends, patients were divided into 6 groups, each corresponding to a 3-year interval within the study period. - Results - Overall, 3,957 patients were included in the study. There was a significant demographic transition, with the proportion of male patients rising from 10% to 15% (P = 0.003). Although apical TTS remained the most common form, the diagnosis of midventricular TTS increased from 18% to 28% (P = 0.018). The prevalence of physical triggers increased from 39% to 58% over the years (P < 0.001). There was a significant increase in 60-day mortality over the years (P < 0.001). However, a landmark analysis excluding patients who died within the first 60 days showed no differences in 1-year mortality (P = 0.150). - Conclusions - This study of temporal trends in TTS highlights a transition in patients demographic with a growing prevalence among men, increasing recognition of midventricular TTS type, and increased short-term mortality and rates of cardiogenic shock in recent years. This transition aligns with the rising prevalence of physical triggers, as expression of increased recognition of TTS in association with acute comorbidities.